Traces of ink : experiences of philology and replication - Raggetti, Lucia (Nuncius series: Studies and sources in the material and visual history of science, 2021)
"Traces of Ink. Experiences of Philology and Replication is a collection of original papers exploring the textual and material aspects of inks and ink-making in a number of premodern cultures (Babylonia, the Graeco-Roman world, the Syriac milieu and the Arabo-Islamic tradition). The volume proposes a fresh and interdisciplinary approach to the study of technical traditions, in which new results can be achieved thanks to the close collaboration between philologists and scientists. Replication represents a crucial meeting point between these two parties: a properly edited text informs the experts in the laboratory who, in turn, may shed light on many aspects of the text by recreating the material reality behind it. Contributors are: Miriam Blanco Cesteros, Michele Cammarosano, Claudia Colini, Vincenzo Damiani, Sara Fani, Matteo Martelli, Ira Rabin, Lucia Raggetti, and Katja Weirauch"--